Crustal and upper mantle velocity structure of Southern Iberia, the sea of Alboran, and the Gibraltar arc determined by local earthquake tomography - M. J. Blanco; J. Mezcua; E. Gurria (Annals of Geophysics, 1997)
A "local earthquake tomography" of a large area encompassing the South of Iberia, the sea of Alboran, the Gibraltar arc, and Northern Morrocco, has been performed using first arrival times recorded at various Spanish and Morroccan seismic networks. A total of 52 stations and 639 earthquakes provided over 6300 first P arrivals and 4400 S arrivals. Three features of interest appear in the results: i) a continuous low velocity structure which correlates with the Betics, the Gibraltar arc and the Rif; ii) a high velocity feature which persists to a depth of approximately 30 km, positioned near the coast of Malaga on the northern margin of the Alboran sea; iii) a low velocity feature, extending to a minimum depth of approximately 40 km, which coincides with the Granada basin and a strong negative Bouguer gravity anomaly.